COVID-19-associated fungal infections - Hoenigl, Martin; Seidel, Danila; Sprute, Rosanne; Cunha, Cristina; Oliverio, Matteo; Goldman, Gustavo H.; Ibrahim, Ashraf S.; Carvalho, Agostinho (Nature microbiology, 2022)
Coronavirus disease 2019 (COVID-19)-associated invasive fungal infections are an important complication in a substantial number of critically ill, hospitalized patients with COVID-19. Three groups of fungal pathogens cause co-infections in COVID-19: Aspergillus , Mucorales and Candida species, including Candida auris . Here we review the incidence of COVID-19-associated invasive fungal infections caused by these fungi in low-, middle- and high-income countries. By evaluating the epidemiology, clinical risk factors, predisposing features of the host environment and immunological mechanisms that underlie the pathogenesis of these co-infections, we set the scene for future research and development of clinical guidance. Hoenigl and colleagues review the epidemiology, immunology and clinical risk factors contributing to COVID-19-associated fungal infections.